THE CORRELATION BETWEEN SIMPLE PRESENT TENSE MASTERY AND DESCRIPTIVE PARAGRAPH WRITING ABILITY - Ni Luh Eka Jayanti; Ni Luh Putu Dian Sawitri; Ida Bagus Nyoman Mantra (Academic Journal on English Studies (AJOES), 2023)
This ex-post facto research aims at figuring out the correlation between simple present tense mastery and descriptive paragraph writing ability of the eighth-grade students of SMPN 3 Gianyar in the academic year 2022/2023. The samples of this research were 80 students from 495 populations of the eighth-grade students at SMPN 3 Gianyar in the academic year 2022/2023, chosen by clustered random sampling technique. The data were collected by administering two research instruments in the form of a sentence writing test and paragraph construction test. Pearson product-moment correlation and t-test by SPSS 25 Version for Windows was used to correlate both simple present tense mastery (variable X) and descriptive paragraph writing ability (variable Y). The data analysis results showed that there was a correlation at (0.630) which is higher than the r-table of significant level at 5% (0.220). To sum up, the present research findings finally confirmed that there was a significant correlation between simple present tense mastery and descriptive paragraph writing ability of the eighth-grade students of SMPN 3 Gianyar in the academic year 2022/2023.